2014
DOI: 10.1371/journal.pntd.0003118
|View full text |Cite
|
Sign up to set email alerts
|

High Fat Diet Modulates Trypanosoma cruzi Infection Associated Myocarditis

Abstract: Background Trypanosoma cruzi, the causative agent of Chagas disease, has high affinity for lipoproteins and adipose tissue. Infection results in myocarditis, fat loss and alterations in lipid homeostasis. This study was aimed at analyzing the effect of high fat diet (HFD) on regulating acute T. cruzi infection-induced myocarditis and to evaluate the effect of HFD on lipid metabolism in adipose tissue and heart during acute T. cruzi infection.Methodology/Principal FindingsCD1 mice were infected with T. cruzi (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
115
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(126 citation statements)
references
References 23 publications
11
115
0
Order By: Relevance
“…Tissue lysates were prepared as previously described [2-5]. An aliquot of each sample (40 μg proteins) was subjected to electrophoresis on a 4-15% gradient SDS-PAGE and the proteins transferred to nitrocellulose filters for immunoblot analysis.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Tissue lysates were prepared as previously described [2-5]. An aliquot of each sample (40 μg proteins) was subjected to electrophoresis on a 4-15% gradient SDS-PAGE and the proteins transferred to nitrocellulose filters for immunoblot analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Chagas disease is a major cause of mortality and morbidity in Latin America, largely due to cardiomyopathy that develops in a large segment of the infected population [1, 2]. Recent research has demonstrated that T. cruzi causes a significant infection in adipocytes and adipose tissue, resulting in changes in adipocyte physiology that affects parasitemia, tissue parasite loads and cardiac pathology [2-4]. A western-style diet that is high in fat and processed foods is becoming prevalent in Latin America, replacing the traditional dietary system, and has been accompanied by an increased incidence of diabetes and obesity in this Chagas Disease endemic region.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Johndrow et al [48] demonstrated that T. cruzi induces increases in intracellular low-density lipoprotein and cholesterol in murine models during the acute and chronic phases of infection by up-regulating the low-density lipoprotein receptor, and they showed similar findings in CCC-affected human heart tissue. Nagajyothi et al [49] showed that a high fat diet in mice alters the host metabolic regulation, leading to parasite sequestration in adipose tissue and a surprising protective effect of decreased mortality, lower levels of parasitemia, and less myocardial damage during acute infection.…”
Section: Nhlbi–funded Research On Chagas Diseasementioning
confidence: 99%